Implementasi Metode Naive Bayes Untuk Klasifikasi Penerima Program Keluarga Harapan - Andhini Asri Awaliyah Arifin; Wiwin Handoko; Zulfan Efendi (LPPM STMIK Royal Kisaran, 2022)
Abstract: The Family Hope Program (PKH) is a government program in the form of cash for Very Poor Households (RTSM) whose qualifications are met related to efforts to improve human quality, not in the field of education but also health. In the short term, the PKH program is calculated to reduce the expenditure of poor families and reduce poverty in the long term. To receive the PKH Program) the government has set several criteria, including income, house ownership status, house size, floor type, roof, wall, and type of water source. As for the way to do the settlement of the criteria that have been set, namely by utilizing the Data Mining technique through the Naïve Bayes method. The dataset in this study is the data of recipients of the 2020 Family Hope Program as many as 82 samples. The results of the classification modeling with the Naïve Bayes Algorithm produce precision values for the positive class 100%, for the negative class 77%, the recall value for the positive class 80%, for the negative class 100%, the f1-score value for the positive class 89%, for the negative class 87%, and 88% accuracy value. The purpose of this research is to help the Social Service in classifying the recipients of the Family Hope Program (PKH). Keywords: The Family Hope Program; Data Mining; Naïve Bayes Abstrak: Program Keluarga Harapan (PKH) merupakan program pemerintah dalam bentuk tunai untuk Rumah Tangga Sangat Miskin (RTSM) yang kualifikasinya terpenuhi terkait dengan upaya peningkatan kualitas manusia tersebut bukan dalam bidang pendidikan tetapi juga kesehatan. dalam jangka pendek Program PKH diperhitungkan bisa mengurangi biaya pengeluaran keluarga miskin serta mengurangi kemiskinan dalam jangka panjang. Untuk menerima Program PKH) pemerintah sudah menetapkan beberapa kriteria, diantaranya Penghasilan, Status Kepemilikan Rumah, Ukuran Rumah, tipe Lantai, Atap, Dinding, serta jenis sumber air. Adapun cara untuk melakukan penyelesaian terhadap kriteria yang sudah ditetapkan yaitu dengan memanfaatkan teknik Data Mining melalui Metode Naïve Bayes. Dataset dalam penelitian ini adalah data penerima Program Keluarga Harapan tahun 2020 sebanyak 82 sampel. Hasil pemodelan klasifikasi dengan Algoritma Naïve Bayes menghasilkan besaran nilai precision untuk kelas positif 100%, untuk kelas negatif 77%, nilai recall untuk kelas positif 80%, untuk kelas negatif 100%, nilai f1-score untuk kelas positif 89%, untuk kelas negatif 87%, dan nilai akurasi 88%. Tujuan dilaksanakannya penelitian ini adalah untuk membantu Dinas Sosial mengklasifikasikan penerima Program Keluarga Harapan (PKH). Kata kunci: Program Keluarga Harapan; Data Mining; Naïve Bayes